Тарих пәнін оқытуда тарихи даталарды есте сақтау жолдарының әдістері - Қылышбекова, Б.Қ. (My University, 2013)
Methods of memorizing historical dates when teaching history. Integrates the psychological methods with the methods of memorizing historical dates propose a new technigue, to make a reception ltarning.